The religious dimension and motivation of modern terrorism (Eurasian Journal of Religious Studies, 2016)
This article is dedicated to one of the most pressing and urgent problems, the problems of contemporary forms of terrorism. Modern terrorism is often «religious» in nature. Due to the fact that terrorism is actively using some doctrinal position of religion – hence created the view that this type of terrorism is religious. Between the religious contradictions and religious fundamentalist movements give special urgency to terrorism, most serious terrorist attacks decades – have a religious dimension and motivation, making it more real danger of a significant destabilization of the world. The scale of terrorism and its destructive potential is so great that it allows us to consider the terrorist activities of one of the global problems of modern civilization.